Student Perceptions of a Hip-Hop Based Community Models Level IFieldwork for Level II Fieldwork Preparedness: A Case Study...National Society of Allied Health Annual Conference and Meeting, March 10-12, 2022, Tallahassee, Florida - Jones, J.; Alexander, A.; Etheridge, J. (Journal of the National Society of Allied Health)
COVID-19 facilitated the revision of curricula and clinical rotation experiences for allied health professional programs. A Master of Science in Occupational Therapy program at a HBCU implemented a simulated community models Level I Fieldwork rotation for the Summer 2021 academic session. The simulated fieldwork rotation replaced the typical in person rotation due to lack of response from partnering sites affected by COVID-19. In an effort to address the need of partnering sites for continuity, students were required to provide the community partnering sites with virtual toolkits that simulated clinical group services. Clinical group services reflected the needs of the population based on secondary qualitative data. Four students created, implemented, and organized a virtual toolkit for a community youth site utilizing a Hip-Hop theme to encourage participation and meaningfulness. This presentation will discuss the foundation of an occupational therapy community model and, the specific program created by the student group including qualitative themes on the perceptions of students for fieldwork Level II readiness.